Dopamin, Media Sosial, dan Generasi Z: Sebuah Tinjauan Biopsikologi Kesehatan Mental Era Digital - Mutia Aini Ahmad; Desmita Desmita; Hidayatul Fikra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Social media has become an integral part of Generation Z's daily life, yet its intensive use has raised concerns regarding mental health. This study aims to systematically examine the relationship between dopamine activity, social media usage, and psychological conditions of Generation Z from a biopsychological perspective. Using a meta-synthesis approach, 20 relevant scientific articles published between 2017 and 2024 were analyzed. The findings reveal five major themes that describe the connection between brain reward systems and digital behavioral patterns among adolescents, including tendencies of addiction, emotional dysregulation, and neurocognitive changes. These results provide a deeper understanding of neuropsychological dynamics in digital contexts and emphasize the need for biopsychological approaches in developing evidence-based mental health interventions. This study is expected to contribute to the advancement of digital psychology and strategies to mitigate the negative effects of social media on adolescents.